Accountability of SDGs in Local Governments: Case Study of Central Java and Yogyakarta - Wulandari, Eva; Sitoresmi, Mumpuni Wahyudiarti; Atika, Atika; Manurung, Herlina; Sunaningsih, Suci Nasehati; Arifah, Siti (Accounting Analysis Journal, 2024)
Purpose: The study explores the work program preparation, budgeting, implementation, and accountability of SDGs targets and achievements by Central Java and Yogyakarta. Method: The research used a qualitative approach and included case studies of the governments of Central Java and Yogyakarta. Data was collected through interviews with the SDGs Implementation Team and study of SDGs documentation, then reduced, presented, and concluded. Findings: The results showed three main themes that reveal accountability SDGs in Central Java and Yogyakarta: preparation and budgeting, implementation and accountability, and strengthening the implementation of SDGs. Those themes explained that the implementation of SDGs by Central Java and Yogyakarta governments are not carried out separately but are attached to programs and activities prepared about the Regional Medium-Term Development Plan. This study is expected to improve integration between central and regional governments so that SDGs can be reported according to actual conditions. Novelty: The research provides an overview of the accountability mechanisms for SDG programs and activities, starting from the planning process, budgeting, and implementation to strengthening. This also reveals the facts SDGs accountability in the field, which demonstrate the legitimacy of local governments towards the commitment of implementation of SDGs.